Overponderabilia: Overcoming Overthinking When Studying "Ourselves" - Vangkilde, Kasper Tang; Sausdal, David Brehm (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2016)
This article discusses a key methodological difficulty in conducting qualitative research close to home: the issue of overthinking. Whereas MALINOWSKI's concern regarding imponderabilia, i.e., the risk of not thinking about the subtle phenomena of everyday life, has long haunted ethnographers and qualitative researchers, not least those working "at home," we highlight an issue of overponderabilia, i.e., the risk of overthinking seemingly familiar statements and practices of the people studied. How do we, as qualitative researchers, study very well-known phenomena such as science, bureaucracy, management etc. without reading our own ideas and understandings into the deceptively familiar concepts and accounts of our research subjects? Pondering this issue is inevitably a central concern for the increasing number of qualitative researchers who study people who apparently talk, think and work in a way which is similar to their own. While previous answers or solutions to this issue first and foremost emphasize various means of reflexivity, this article presents the method of "mutual participatory observation" as a particular way of overcoming overthinking: a method which in situ invites our research subjects into our thinking. Thus, in the pursuit of an ever enhanced understanding, qualitative research becomes not so much a reflexive deciphering as an active debate; that is, a mutual induction of the differences between the qualitative researcher and the research subjects. URN: http://nbn-resolving.de/urn:nbn:de:0114-fqs1602281